Asistensi penataan aset Desa Cibugel untuk tata kelola aset yang lebih baik - Biswan, Ali Tafriji; Imapo, Yanuar Fiskar; Prayoga, Akhdan Nur; Emmir, Arga; Hany, Sharah Puan (PT WIM Solusi Prima, 2025)
Village asset management plays a critical role in ensuring accountable and sustainable public service delivery at the grassroots level. However, Desa Cibugel in Tangerang Regency faces significant challenges in managing its village-owned assets, including incomplete documentation, weak inventory systems, and limited understanding among local officials regarding asset maintenance and related tax obligations. This community engagement project aimed to enhance asset governance by providing structured assistance in asset recording, labeling, maintenance scheduling, and the development of a basic asset monitoring dashboard using digital tools. The methodology consisted of four stages: initial observation, solution design, on-site implementation, and evaluation. Key outputs included inventory and maintenance cards, a monitoring spreadsheet, and a Google Sites-based dashboard tailored to the village’s needs. The intervention resulted in improved awareness among village officials regarding asset accountability and demonstrated a practical, low-cost model for achieving administrative order in asset management. The project shows that university-community collaboration can significantly contribute to optimizing village governance, especially when reinforced with contextualized tools and participatory methods. Pengelolaan aset desa merupakan aspek penting dalam tata kelola keuangan desa yang akuntabel dan berkelanjutan. Namun, di Desa Cibugel, Kabupaten Tangerang, masih ditemukan berbagai kendala seperti lemahnya pencatatan aset, kurangnya pemahaman siklus pengelolaan aset, serta belum optimalnya pemanfaatan teknologi informasi. Kegiatan pengabdian ini bertujuan untuk memberikan asistensi dalam penatausahaan aset melalui pemetaan masalah, pendataan ulang aset, pelabelan, serta penyusunan kartu inventaris dan pemeliharaan. Metode yang digunakan meliputi observasi awal, penyusunan solusi, implementasi lapangan, dan evaluasi. Luaran kegiatan meliputi format kartu pemeliharaan, database monitoring aset, serta dashboard sederhana melalui platform Google Sites. Hasilnya menunjukkan peningkatan pemahaman perangkat desa terhadap prinsip dasar penataan aset, kesadaran terhadap kewajiban pemeliharaan dan pajak aset, serta dokumentasi aset yang lebih tertib. Kegiatan ini membuktikan bahwa pendampingan berbasis kolaboratif antara perguruan tinggi dan desa dapat memperkuat tata kelola aset desa secara signifikan.